Taxonomic, Phylogenetic and Functional Diversity of Bird Assemblages in Urban Green Spaces: Null Model Analyses, Temporal Variation and Ecological Drivers - Nava-Díaz, Remedios; Zuria, Iriana; Pineda-López, Rubén (Frontiers in Ecology and Evolution, 2022)
Urban expansion is a pervasive driver of biodiversity loss. To understand the effects of urbanization on diversity, we investigated the response of bird taxonomic, phylogenetic, and functional diversity to urban green spaces’ characteristics in thirty-one green spaces of Mexico City. Selected sites encompassed variation of environmental factors along a transformation gradient, from natural protected areas to landscaped parks. Bird observations were conducted during winter (non-breeding season), spring (dry breeding season), and summer (wet breeding season). We used multi-model inference to assess the relationship of green space area, shape, isolation, tree richness, habitat diversity, and vegetation cover with species richness, Faith’s phylogenetic diversity, and functional richness. We calculated standardized effect sizes from null models to assess phylogenetic and functional structure. We registered 91 species belonging to 28 families across all sites and seasons. The number of detected species was largest in winter and decreased towards the dry breeding season, and then towards the wet breeding season. We found a moderate to strong positive relationship of species richness with phylogenetic diversity and functional richness. Overall, phylogenetic and functional structure of bird communities in green spaces was neither clustered nor over-dispersed. However, few cases of functional clustering, phylogenetic clustering, or both were observed, and they corresponded to natural protected areas. Results showed a predominant role of green space area in determining community diversity and phylogenetic structure while it did not influence functional structure. Contrary to our predictions, habitat diversity had a negative effect on species richness and phylogenetic diversity and this effect was detected only during the wet breeding season, whereas isolation showed a positive relationship with phylogenetic and functional structure, during the wet breeding season and winter, respectively. This study emphasizes the use of complementary measures of diversity together with the comparison between observed and expected values to get a better insight into the mechanisms by which green spaces’ characteristics affect bird diversity across the seasons.